Level Of Dribbling Skills In Futsal Games Among Extracurricular Players Of Himajas Putri At Dehasen University Bengkulu - Donika Restami; Roni Syaputra; Feby Elra Perdima (Utami Publisher, 2026)
This study aims to determine the level of dribbling skills in futsal games in extracurricular players of female Himajas at Dehasen University, Bengkulu with a quantitative descriptive research type with a sample of 20 players. The data collection instrument uses a standardized dribbling skills test. The results of the study show that the futsal dribbling skills of female Himajas players obtained the fastest value of 8.76 and the lowest value of 17.23 with an average of 13.03 in the moderate category. Futsal dribbling skills of female Himajas players are in the good and moderate categories with data acquisition in the